Pricing the digital version of a book: wholesale vs. agency models. Issue 2 (3rd April 2018) - Luo, Chunlin; Leng, Mingming; Tian, Xin; Song, Jingpu
Abstract: We investigate the wholesale and agency pricing models for the digital version of a book made by a publisher, when the print version of the book may exist and one or two retailers sell the book in a market. In the monopoly and duopoly settings, if the revenue-sharing ratio is sufficiently high and the tax rate for the digital version is sufficiently low, then the retail price of the digital version under the agency model is smaller than that under the wholesale model. We also find that the retail price of the digital version under the agency pricing model is more likely to be above that under the wholesale pricing model in the duopoly setting than in the monopoly setting. In the duopoly setting, a sufficiently small degree of substitutability between the two book versions can also make the retail price of the digital version smaller under the agency model than under the wholesale model. Moreover, the existence of the print version is helpful to reducing the retail price of the digital version.